Nutritional Challenges and Eating Habits in Children with Sensory Processing Disorders - Moore, Isabella (Psychological Research in Individuals with Exceptional Needs, 2024)
The objective of this study was to explore the nutritional challenges and eating habits of children with Sensory Processing Disorders (SPD) through qualitative analysis. The focus was on identifying specific sensory sensitivities, emotional and behavioral impacts, and effective management strategies to improve nutritional outcomes. This qualitative study involved semi-structured interviews with caregivers of 20 children aged 4-12 years diagnosed with SPD. Participants were recruited from pediatric therapy centers, support groups, and online forums. Data were collected until theoretical saturation was reached. The interviews were transcribed and analyzed using thematic analysis to identify key themes and patterns related to eating behaviors and nutritional challenges. The analysis revealed five main sensory challenges impacting eating habits: texture sensitivity, taste sensitivity, smell sensitivity, visual sensitivity, and temperature sensitivity. Emotional and behavioral impacts included mealtime anxiety, food refusal, and social isolation. Various strategies were employed by parents and professionals to manage these challenges, such as implementing food routines, gradual food exposure, and sensory integration therapy. The study also highlighted nutritional deficiencies and growth concerns associated with restricted diets in children with SPD, as well as success stories where tailored interventions led to improvements in eating habits and overall nutritional status. Children with SPD face significant sensory, emotional, and behavioral challenges that impact their eating habits and nutritional intake. Tailored interventions that address individual sensory profiles and involve a collaborative approach between parents, educators, and healthcare professionals are crucial for managing these challenges effectively. The study underscores the need for ongoing research and practical strategies to support better nutritional outcomes for children with SPD.